Management of the Mastoid Cutaneous Fistula - Rajkumari P. Khatri (Current Progress in Medicine and Medical Research Vol. 5, 2023)
This chapter highlights to develop an effective technique for the closure of the mastoid cutaneous fistula and to prevent the recurrence of the fistula & avoid further complications. A uncommon chronic otitis media (COM) consequence called post-auricular mastoid cutaneous fistula (PAMCF) can develop after difficult mastoid surgery and extremely infrequently after congenital cholesteatoma. Due to necrotic skin edges, simple closures have a significant failure risk. Therefore, several techniques for the closure of this fistula have been described. Post aural fistula after canal wall down (CWD) mastoidectomy can be successfully treated by fistula tract excision and obliterating the mastoid cavity. The mastoid-cutaneous fistula after mastoid surgery requires regional flaps for repair and a vascularized flap to prevent the necrosis of avascular tissue because there is insufficient tissue locally to repair the fistula. The fistula developed secondary to the disease can be managed surgically along with the disease. The PAMCF, following radical mastoidectomy surgery, may occur due to non-compliance of the patient, not gone for follow up following radical mastoidectomy, recurrence of the disease, residual disease. Post auricular incision is given encircling the fistulous opening. Anterior and posterior flaps are elevated. The fistulous tract extending into the mastoid cavity is removed in toto.The incomplete disease clearance during mastoidectomy has been recognized as a common cause of failure in patients, with or without cholesteatoma. The anteriorly based vascularized pedicled temporalis muscle flap ensures the viability of the flap and prevents the necrosis of the skin edges, thereby preventing the recurrence of the fistula. The temporo-mastoid fascio-cutaneous-periosteal advancement flap is effective for proper closure of the fistula and obliteration of the cavity by conchal cartilage.